KEABSAHAN ALAT BUKTI ELEKTRONIK BERUPA REKAMAN DALAM PROSES PEMBUKTIAN DI DALAM PENEGAKAN HUKUM PIDANA (STUDI KASUS PUTUSAN NOMOR : 661/PID.B/2016/PN.BLB) - Ricky Vandre Teguh Jaya; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2020)
Evidence comes to determine that whether or not a person is convicted, Research Method used is normative research using statutory and analytical approach, data collection through literature studies, The research about evidence that use on criminal cases, there are many evidence in Criminal Procedure Code, Article 184 in Criminal Procedure Code acknowledges that there are 5 pieces of evidence, however, evidence based on electronic data its not comes from Criminal Procedure Code, its come from different law constitution,Law of Republic Indonesia Number 19 Year 2016 concerning Information and Transaction Electronic in article 5 is about evidence electronic that valid to use as an evidence such as evidence in Criminal Procedure Code article 184, therefore electronic evidence is valid and legal to use on criminal cases, the recruitment of electronic evidence on article 5 to becomes legal evidence that got recognize by the judge is still not clear, so there is needed to increasingly emphasized that electronic evidence.